Designing A Typeface Inspired by The Embunbekhangkat Motif of The Alas Tribe, Southeast Aceh - Firman; Yuliarni, Yuliarni; Akmal, Ahmad (TEXTURE Art and Culture Journal, 2025)
This research aims to design a decorative typeface inspired by the Embunbekhangkat motif of the Alas tribe in Southeast Aceh, as an effort to preserve local culture and strengthen regional visual identity. The study applies a qualitative creation method including literature study, observation, interview, and visual analysis using the 5W+1H approach. The resulting typeface, named ‘Mesikhat,’ was designed through ideation, stylization, digitization, and application stages. The typeface is categorized as a display font with decorative features while maintaining legibility, readability, and clarity. The final result is a digital typeface in OTF and TTF formats applicable in various media such as posters, packaging, and cultural merchandise, supporting the promotion of Southeast Aceh’s cultural identity.